Clonally resolved single-cell multi-omics identifies routes of cellular differentiation in acute myeloid leukemia - Beneyto Calabuig, Sergi; Merbach, Anne Kathrin; Kniffka, Jonas-Alexander; Antes, Magdalena; Szu-Tu, Chelsea; Rohde, Christian; Waclawiczek, Alexander; Stelmach, Patrick; Gräßle, Sarah; Pervan, Philip; Janssen, Maike; Landry, Jonathan J. M.; et al. (Cell stem cell, 2023)
acute myeloid leukemia, leukemic stem cells, cancer stem cells, hematopoietic stem cells, cellular differentiation, AML, LSC, CSC, HSC, single-cell RNA-seq, computational biology, single-cell genomics, single-cell transcriptomics, computational method